Pengaruh Naphthalene Asam Asetat (NAA) pada Pertumbuhan Akar Pisang Raja Kinalun Secara In Vitro - Rahmi Rini Dwi Putri; Suwirmen Suwirmen; Nasril Nasir (Jurnal Biologi Universitas Andalas, 2018)
The influence of Naphthalene Acetate Acid (NAA) on the in vitro root growth of banana Raja Kinalun was carried out from April to September 2015 in The Laboratories of Plant Physiology and Tissue Culture, Faculty of Mathematics and Natural Sciences, University of Andalas, Padang. The aim of  this study was to find the effective concentration of NAA for initiation of root. This study used a Completely Randomized Design (CRD) with four treatments and three replications. The treatments were: without NAA (control); NAA 1 ppm, NAA 2 ppm and NAA 3 ppm. The result showed that the effective doses were NAA 1 and 2 ppm for each number of roots growth.